A study on the energy absorption properties of carbon/aramid fiber filament winding composite tube. (May 2015) - Ma, Yan; Sugahara, Toshi; Yang, Yuqiu; Hamada, Hiroyuki
Abstract: Fiber reinforced composites (FRPs) with light weight did not exhibit the ductile failure mechanism which was related to metals. FRPs absorb lots of energy through progressive crushing modes by a combination of multi micro-crack, bending, delamination and friction. FRPs with half weight of traditional metals while absorb more than doubled energy. But FRPs were not used as energy absorption components in wide range; one of the most important reasons is their high manufacturing cost. In this study, carbon fiber and aramid fiber were chosen as reinforcements and common epoxy resin was chosen as matrix to manufacture five types of different structures and raw materials of carbon/aramid and carbon/carbon fiber reinforced composite tubes through high productive and low cost winding method. Then specimens were dealt under 100 °C condition for 100 h, 200 h and 400 h treatment respectively. After that, energy absorption ability was tested by quasi static compression tests and microscope observation of cross section was taken to analyze the mechanism of failure. By optimizing different hybrid method, ratio and reasonable geometry shape of composites, low cost and high energy absorption components whose specific energy absorption ( Es ) were near 100 kJ/kg could be manufactured to put to use on vehicles.